Investigating the Academic Progress of Namcol Tertiary Programme Students Admitted Through Recognition of Prior Learning 2019-2020 - Amakali, Victoria Magano (International Journal of Scientific Research and Management (IJSRM), 2024)
The intention of this study was to report on the progress of students admitted through the Recognition of Prior Learning (RPL) for the academic year 2019 and 2020 at the Namibian College of Open Learning (NAMCOL). The experience of students admitted through RPL seems under researched, given the number of limited studies undertaken at Higher Education Institutions (HEIs) offering Open and Distance Learning (ODL). The study aimed to explore the progress of students admitted to certificate programmes offered by NAMCOL through RPL. This study used Abraham Maslow’s Need Theory as a theoretical framework. The research followed a qualitative research method. A descriptive research design was employed for the study. The population comprised certificate students admitted through RPL during the 2019 and 2020 academic years. Purposeful sampling technique which comprised a sample of 30 students was used. Data were collected through a structured interview guide. Students ‘academic records were reviewed to determine their progress. Data were analysed and presented thematically. Main outcomes of the study showed that several factors affect students’ performance positively and negatively. Factors contributing positively include the delivery of face-to-face contact sessions and discussions with other students. Aspects contributing negatively to the academic success of students include distance, work, and family responsibilities. The study, therefore, recommends that more face-to-face contact sessions should be made available to students. These could be offered online synchronously or asynchronously to enable students to play and review sessions on their own time.